Improving Employee Performance Through Good Organizational Culture and Work Motivation - Shalahuddin Shalahuddin (Advances in Human Resource Management Research, 2022)
This research was conducted at the Office of Transportation in Buukumba Regency. The aims of this study are (1) to analyze the influence of organizational culture on the performance of the Transportation Service Employees in Bulukumba Regency, (2) to analyze the influence of motivation on the Transportation Service Employees' performance in Bulukumba Regency. The population in this study were all employees of the Department of Transportation in Bulukumba Regency with a total sample of 58 people. Data collection methods used are interviews, documentation, and questionnaires. The data analysis method of this research uses instrument test (validity test and reliability test), descriptive analysis, multiple regression analysis, partial hypothesis testing (t) and simultaneous test (F) and the coefficient of determination. The conclusion of this research is that organizational culture and motivation have a significant effect on the performance of the Department of Transportation employees in Bulukumba Regency. We suggest that the Head of the Department of Transportation should always appreciate every achievement that has been achieved by its employees because the statement "The Organization (Leadership) rewards innovation or achievements you make at work" has a fairly low response, meaning that employees need awards for their achievements, because giving awards can improve the performance of good employees